TANGGUNG JAWAB NOTARIS DALAM PEMBUATAN AKTA PERJANJIAN PENGIKATAN JUAL BELI TANAH YANG MENGATUR KLAUSUL JUAL BELI DENGAN HAK MEMBELI KEMBALI - Elisabeth Novena; Maryano; Putra Hutomo; Maryano Maryano (Journal of Innovation Research and Knowledge, 2025)
A notary holds an essential role in drafting the Land Sale and Purchase Binding Agreement (PPJB). Issues arise regarding the buy back clause as regulated in the Indonesian Civil Code (KUHPerdata). De facto, this clause is no longer relevant following the enactment of the Basic Agrarian Law (UUPA). In practice, it is found that notaries sometimes prepare PPJBs whose provisions contradict agrarian law principles and are disguised as loan agreements. This research examines two main issues: (1) What are the legal consequences of a PPJB deed that regulates a sale and purchase agreement with a buy-back clause? (2) What are the responsibilities of a notary in drafting a PPJB deed that includes a sale and purchase agreement with a buy back clause? The analysis in this research employs the Theory of Legal Consequences by R. Soeroso and the Theory of Legal Responsibility by Hans Kelsen. The method used in this research is normative juridical research, especially Library Law research or secondary data with primary, secondary and tertiary sources of law. The research approaches used include legislative approaches, case studies, conceptual, and analytical methodologies. And the method of collecting such legal materials is carried out by identifying and inventorying positive law, journals and other sources of law. The method used in analyzing the material of grammatical laws and systematic interpretation. The research findings indicate that a Land Sale and Purchase Binding Agreement (PPJB) containing a buy back clause is null and void by law, as it contradicts agrarian law and is misused as a loan agreement A notary who fails to ensure the conformity of the deed with the actual facts may be held administratively and civilly liable under the Articles 84 and 85 of Indonesian Notary Law (UUJN). Therefore, notaries are obliged to provide legal counseling and exercise due diligence to prevent the misuse of PPJB, and regulators should amend Article 17 of the UUJN concerning the prohibition for notaries, specifically prohibiting notaries from drafting a PPJB of land with a buy-back clause.